Glabridin induces overexpression of two major apoptotic genes, MCA1 and NUC1, in Candida albicans. (December 2017) - Nabili, Mojtaba; Moazeni, Maryam; Hedayati, Mohammad Taghi; Aryamlo, Parisa; Abdollahi Gohar, Atefeh; Madani, Seyed Mehdi; Fathi, Hamed
Highlights: Glabridin inhibits the growth of fluconazole-resistant Candida albicans at low MICs. Glabridin-treated C. albicans cells showed overexpression of MCA1 and NUC1 genes. Upregulation of MCA1 and NUC1 may cause apoptosis induction in C. albicans . Abstract: Objectives: The growing trend in emergence of antifungal-resistant Candida strains has recently inspired researchers to design new antifungal agents with novel mechanisms of action. Glabridin is a natural substrate with multiple biological activities. In this study, the antifungal effects and possible mechanism of action of glabridin were investigated. Methods: Minimum inhibitory concentrations (MICs) of glabridin against fluconazole (FLU)-resistant and FLU-susceptible Candida albicans strains were investigated according to Clinical and Laboratory Standards Institute (CLSI) guidelines. To investigate the possible mechanism of action, expression of two critical genes involved in yeast apoptosis ( MCA1 and NUC1 ) was assayed by real-time PCR. Results: FLU-susceptible and FLU-resistant C. albicans strains showed the same glabridin MICs (MIC50, 8 μg/mL). Therefore, a distinct azole-independent mechanism might be responsible for the inhibitory activity of glabridin. Overexpression of MCA1 and NUC1 was observed in C. albicans cells treated with glabridin, suggesting the involvement of apoptosis signalling in C. albicans strains exposed to glabridin. Conclusion: This study suggests that glabridin might be considered a safe agent to fight against C. albicans strains.